The influence of different sizes and types of wound fillers on wound contraction and tissue pressure during negative pressure wound therapy. - Anesäter, Erik; Borgquist, Ola; Hedström, Erik ; 0000-0003-0041-9357; Waga, Julia; Ingemansson, Richard; Malmsjö, Malin (International Wound Journal, 2011)
Negative pressure wound therapy (NPWT) contracts the wound and alters the pressure in the tissue of the wound edge, which accelerates wound healing. The aim of this study was to examine the effect of the type (foam or gauze) and size (small or large) of wound filler for NPWT on wound contraction and tissue pressure. Negative pressures between -20 and -160 mmHg were applied to a peripheral porcine wound (n = 8). The pressure in the wound edge tissue was measured at distances of 0·1, 0·5, 1·0 and 2·0 cm from the wound edge and the wound diameter was determined. At 0·1 cm from the wound edge, the tissue pressure decreased when NPWT was applied, whereas at 0·5 cm it increased. Tissue pressure was not affected at 1·0 or 2·0 cm from the wound edge. The tissue pressure, at 0·5 cm from the wound edge, was greater when using a small foam than when using than a large foam. Wound contraction was greater when using a small foam than when using a large foam during NPWT. Gauze resulted in an intermediate wound contraction that was not affected by the size of the gauze filler. The use of a small foam to fill the wound causes considerable wound contraction and may thus be used when maximal mechanical stress and granulation tissue formation are desirable. Gauze or large amounts of foam result in less wound contraction which may be beneficial, for example when NPWT causes pain to the patient.